Metacognitive and critical thinking practices in developing EFL students’ argumentative writing skills - Murtadho, Fathiaty (Indonesian Journal of Applied Linguistics, 2021)
This action research examined the roles of writing instruction involving metacognitive and critical thinking strategy to improve argumentative writing skills of college students in Indonesia. Argumentative writing is one of the pivotal topics among researchers investigating ways to improve college-level writing. This study involved 88 students of three parallel classes enrolled in the writing skill development course. Employing Kemmis and McTaggart's (1988, 2014) model of action research, this study employed a three-cycle action study in one semester, covering four stages of learning tasks: understanding of problem, monitoring of students’ learning activities, problem-solving, assessment, and conclusion drawing. Each cycle provided learning exercises of metacognitive and critical thinking to hone the students’ argumentative writing skills. Referring to critical skill criteria as a baseline, the analysis found that employing metacognitive and critical thinking process in the instructional treatments enabled the students to improve their argumentative writing skills. The finding indicates a pivotal role of incorporating metacognition in writing instruction as a strategy to improve college-level writing skills.